2014
DOI: 10.2217/fon.14.108
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin/5-Fluorouracil in Advanced Hepatocellular Carcinoma: Case Report and Single-Center Retrospective Review

Abstract: In advanced hepatocellular carcinoma, FOLFOX can induce clinically relevant responses, but needs prospective validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The median OS of 8 months in the present study is longer than that in Goldstein’s (median OS: 6.3 months) and Ogasawara’s (median OS: 7.2 months) reported for patients with sorafenib-refractory advanced HCC. 21,22 That is also longer than that of Asia-Pacific trial (median OS: 6.5 months). 6 Especially for the patients with lower liver tumor burden, extrahepatic metastasis, and had a PR to apatinib, the median OS reached to 16 months, 18 months, and 19 months, respectively, which is significantly longer than that of other studies.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The median OS of 8 months in the present study is longer than that in Goldstein’s (median OS: 6.3 months) and Ogasawara’s (median OS: 7.2 months) reported for patients with sorafenib-refractory advanced HCC. 21,22 That is also longer than that of Asia-Pacific trial (median OS: 6.5 months). 6 Especially for the patients with lower liver tumor burden, extrahepatic metastasis, and had a PR to apatinib, the median OS reached to 16 months, 18 months, and 19 months, respectively, which is significantly longer than that of other studies.…”
Section: Discussionmentioning
confidence: 90%
“…Although some cytotoxic chemotherapies and targeted therapies, such as capecitabine, Leucovocin and oxaliplatin (FOLFOX), epirubicin, cisplatin, and cetuximab, are also used in the treatment of sorafenib-refractory advanced HCC, associated morbidities, such as neutropenia, thrombocytopenia, and gastrointestinal toxicity, frequently occur. 20 22 More serious toxicities, including cytotoxicity-related neutropenic sepsis and liver injury, have also been reported after treatment. 21 However, in the present study, patients treated with apatinib for sorafenib-refractory HCC did not experience treatment-related death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 The ORR was also higher than those reports in patients with sorafenib-refractory HCC. 27 29 The most likely explanation for the improvement of survival outcomes by apatinib treatment among patients with sorafenib-resistant HCC may be the antitumor angiogenic actions of apatinib that occur via its selective inhibition of VEGFR-2, with a binding affinity that is 10 times higher than that of sorafenib. 15 , 16 In contrast, because its anti-VEGFR2 ability is one-tenth that of apatinib, sorafenib is inefficient against sorafenib-resistant HCC.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 5-FU is still being widely used for the treatment of advanced HCC [ 4 ]. Unfortunately, success of a single or combination chemotherapy regimen is mostly transient and modest [ 21 , 22 ]. The present study showed that the combination of AZD8055, but not of everolimus, with 5-FU significantly decreased tumor cell viability compared with single-drug treatment.…”
Section: Discussionmentioning
confidence: 99%